2017
DOI: 10.1038/s41522-017-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Norgestimate inhibits staphylococcal biofilm formation and resensitizes methicillin-resistant Staphylococcus aureus to β-lactam antibiotics

Abstract: A correction to this article has been published and is linked from the HTML version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We also identified enolase, a cytoplasmic glycolytic enzyme, among the ECM proteins ( Table 3 ). Recently, it has been suggested that some cytoplasmic proteins, including enolase, are released from the cytoplasm and are associated with the cell surface, serving as moonlighting ECM components ( Huberts and van der Klei, 2010 ; Henderson and Martin, 2013 ; Yoshii et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also identified enolase, a cytoplasmic glycolytic enzyme, among the ECM proteins ( Table 3 ). Recently, it has been suggested that some cytoplasmic proteins, including enolase, are released from the cytoplasm and are associated with the cell surface, serving as moonlighting ECM components ( Huberts and van der Klei, 2010 ; Henderson and Martin, 2013 ; Yoshii et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is a Gram-positive bacterium that typically colonizes the surface of the skin and, as an important pathogen of nosocomial cross-infection, it is also a common pathogenic bacterium of biofilm infections (1,2). More than 80% of human infections are caused by biofilms, including endocarditis, osteomyelitis and implant-associated infections (3).…”
Section: Introductionmentioning
confidence: 99%